Academic Business Incubators as an institutional form of academic entrepreneurship development in Poland - Lukasz Siemieniuk (Institute of Economic Research (IER), 2015)
The Academic Business Incubators are a significant investment in the development of academic entrepreneurship in Poland. They put the emphasis especially on local development. They are the driving force and a source of motivation to take up new challenges for young people. They allow ambitious people to combine their theoretical knowledge acquired during their studies with practical knowledge. Thanks to the Academic Entrepreneurship Incubators young people become professionals in their actions. Their acquired skills, knowledge, physical, moral and mental characteristics are an excellent basis for the development of their business.The aim of the paper is to discuss the essence of academic entrepreneurship and present issues of the Academic Business Incubators functioning as an institutional form of academic entrepreneurship development in Poland.
Keywords: D01; 330; Business Incubators; academic entrepreneurship; Poland